2019
DOI: 10.1039/c9sc02021g
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-induced super-assembly of biocatalytic metal–organic frameworks for programmed enzyme cascades

Abstract: Complementary peptide-induced super-assembly of biocatalytic MOFs is developed for programmed enzyme cascades on demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 53 publications
1
91
0
Order By: Relevance
“…It has been demonstrated that both of the GOx and Cyt C were uniformly embedded within the ZIF‐8 exoskeleton (Figure C and D). Previous studies have proven that small molecules, or even molecules slightly larger than the window size of ZIF‐8, are able to permeate into ZIF‐8 crystals due to the inherited flexibility of ZIF‐8 and larger defects induced by enzyme loading . Here, N 2 adsorption experiments demonstrated that the pores of the ZIF‐8 exoskeleton remained open (Figure S8A) and the unique porous structure of ZIF‐8 remained intact for both, Cyt C@ZIF‐8 and GOx@ZIF‐8 (Figure S8B).…”
Section: Resultsmentioning
confidence: 70%
“…It has been demonstrated that both of the GOx and Cyt C were uniformly embedded within the ZIF‐8 exoskeleton (Figure C and D). Previous studies have proven that small molecules, or even molecules slightly larger than the window size of ZIF‐8, are able to permeate into ZIF‐8 crystals due to the inherited flexibility of ZIF‐8 and larger defects induced by enzyme loading . Here, N 2 adsorption experiments demonstrated that the pores of the ZIF‐8 exoskeleton remained open (Figure S8A) and the unique porous structure of ZIF‐8 remained intact for both, Cyt C@ZIF‐8 and GOx@ZIF‐8 (Figure S8B).…”
Section: Resultsmentioning
confidence: 70%
“…Previous studies have proven that small molecules,oreven molecules slightly larger than the window size of ZIF-8, are able to permeate into ZIF-8 crystals due to the inherited flexibility of ZIF-8 and larger defects induced by enzyme loading. [16,32,33] Here,N 2 adsorption experiments demonstrated that the pores of the ZIF-8 exoskeleton remained open ( Figure S8A) and the unique porous structure of ZIF-8 remained intact for both, Cyt C@ZIF-8 and GOx@-ZIF-8 ( Figure S8B). Them olecular size of H 2 O 2 as guest molecule for Cyt C@ZIF-8 (low activity) is smaller than that of glucose,t he guest molecule for GOx@ZIF-8 (higher activity).…”
Section: Denaturation Of Enzymes In the De Novo Embedding Strategymentioning
confidence: 99%
“…Reprinted with permission. [41] Copyright 2019, The Royal Society of Chemistry. protected the natural enzymes from the digestion of trypsin and demonstrated unique stability in vitro and in vivo.…”
Section: Compartmentalizationmentioning
confidence: 99%
“…Very recently, our group developed a smart and stimulus-responsive approach to position discrete biocatalytic MOF nanoparticles via complementary peptide interaction (Figure 5c, i). [41] GOx, HRP or β-Gal were first separately encapsulated in ZIF-8 particles via one-step biomineralization method. Utilizing a post-ligand exchange approach, amine groups were then functionalized on the single-enzyme-containing ZIF-8.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
See 1 more Smart Citation